EXPLORING EMBRYOGENIC COMPETENCE IN ANTHERS OF BITTER GOURD (MOMORDICA CHARANTIA L.) CULTIVAR FAISALABAD LONG - M. Usman; K. Bakhsh; B. Fatima; Q. Zaman; M. H. Shah (Journal of Animal and Plant Sciences, 2015)
Haploid plant development through androgenesis is highly genotype dependent. Hence, native high yielding bitter gourd cultivar Faisalabad long was explored for androgenesis and development of embryogenic calli from somatic tissues. Flower buds of different sizes (small 11-13 mm; medium 13-15 mm; large 15-17 mm in length) at popcorn stage were collected. The floral buds ranging from 13-15 mm in size higher percentage of uninucleate microspores compared with other sizes. Cold pretreatment of anthers at 4°C up to 48 hours and cultures under dark conditions significantly enhanced callus induction (71% and 45%) response compared with cultures under long days on MS media supplemented with NAA and BAP (3.22+0.88 µML-1). Rest of the PGRs used did not induce calli. Anther derived calli showed development of embryogenic masses upon transfer to starvation media (½MS salts), however the embryos did not develop further and could not germinate. Hence, further studies are suggested for better embryo germination and maturation.
Keywords: anthers; callogenesis; NAA; bitter melon